Cenários de inﬂação inseridos em extensões do modelo padrão de partículas - Rodrigues, Jamerson Gillis Batista (2019)
With the development of satellites experiments, the inﬂationary paradigm has conquered the status of precision physics. Data obtained from cosmic microwave background (CMB) canbe used to vinculate parameters of inﬂationary models. In this thesis we present our contribuitions to the development of this scenario (1, 2). In particular, we develop a variation of the SU(3)C × SU(3)L ×U(1)N gauge model, proposed originally in (3). This scenario is constructed in a way to address the type-I seesaw and the Peccei-Quin symmetry naturally. Inﬂation is ruled at high energies by the Φ ﬁeld, through radiative corrections in the potential. In the following, we develop a model of non-minimal inﬂation, originally proposed in (2). In this scenario, the neutral component of the ∆ ﬁeld, triplet by SU(2)L, performs inﬂation through a non-minimal coupling to gravity. When the inﬂaton acquires vacuum expected value, mass for the standard neutrinos is generated through type-II seesaw mechanism. When we confront these models with the observed CMB data, we get extremely predictive scenarios, with new signatures on energy scales accessible for future experiments.